2015
DOI: 10.3109/0886022x.2015.1088336
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of rapid onset ESRD accounted for high hemodialysis catheter use—results of a 13-year Mayo Clinic incident hemodialysis study

Abstract: SORO-ESRD accounted for 149 (10%) of 1461 incident ESRD patients. There was no gender disparity. The older population was more susceptible. Ninety-nine percent (99%) of SORO-ESRD patients started their first hemodialysis treatment via a dialysis catheter, a major negative impact on AV fistula first programs. ATN was the leading pathologic diagnosis. We conclude that SORO-ESRD contributes significantly to incident ESRD here in the USA including renal allograft loss. Efforts to reduce AKI incidence or renopreven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Onuigbo et al 24 investigated an incident hemodialysis cohort at Mayo Clinic, Rochester, between 2001 and 2013, and reported the newly described syndrome of rapid onset ESRD (SORO-ESRD) following acute kidney injury (AKI), which was related to subsequent cardiovascular mortality with high rates of dialysis catheter use. 25 In these studies, however, no information has been provided on patients with increasing eGFR and on the association of change in eGFR with different causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Onuigbo et al 24 investigated an incident hemodialysis cohort at Mayo Clinic, Rochester, between 2001 and 2013, and reported the newly described syndrome of rapid onset ESRD (SORO-ESRD) following acute kidney injury (AKI), which was related to subsequent cardiovascular mortality with high rates of dialysis catheter use. 25 In these studies, however, no information has been provided on patients with increasing eGFR and on the association of change in eGFR with different causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid decline in kidney function to ESRD was considered to have occurred if a patient was documented to have estimated GFR >30 mL/min/1.73 m 2 within 3 months prior to the initiation of chronic dialysis . Incidentally, we must observe here that their definition very closely mirrored our standard definition of SORO‐ESRD . Lee et al revealed that 8 of 105 incident chronic dialysis patients in one dialysis unit (7.6%; 95% confidence interval [CI] 3.4%–14.5%) and 9 of 71 incident patients at another dialysis unit (12.7%, 95% CI 6.0%–22.7%), suffered rapid yet permanent decline in kidney function consistent with SORO‐ESRD …”
Section: Introductionmentioning
confidence: 84%
“…In November 2014, we conducted a retrospective analysis of individual patient‐level serum creatinine trajectories of all ESRD patients on maintenance hemodialysis for longer than 90 days at Mayo Clinic, Rochester, between January 1, 2001 and December 31, 2013. Details of the methodologies and logistics of this analysis have been previously described . The objective was to determine the incidence of SORO‐ESRD in our 13‐year ESRD hemodialysis cohort and to further analyze the impact of this syndrome specifically as it relates to renal transplant recipients (RTRs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A just published report from Saudi Arabia revealed an association of continued angiotensin blockade with hospital-acquired AKI (15). Besides, we had demonstrated in a 13-year retrospective analysis of 1461 ESRD patient managed at Mayo Clinic, Rochester, 2001-2013, an incidence rate of SORO-ESRD of 10% but we were not able to show any association between SORO-ESRD and concurrent angiotensin blockade (21). Finally, we would call for caution in the use of angiotensin blockade in older (>65-year old) patients with advanced CKD.…”
Section: Lorffab and Soro-esrdmentioning
confidence: 96%